2023
DOI: 10.1186/s40001-022-00955-x
|View full text |Cite
|
Sign up to set email alerts
|

Survival outcome among patients with out-of-hospital cardiac arrest who received cardiopulmonary resuscitation in China: a systematic review and meta-analysis

Abstract: Background This study aimed to assess the survival outcomes among patients with out-of-hospital cardiac arrest (CA) who received cardiopulmonary resuscitation (CPR) in China. Methods Relevant studies, published between January 1, 2010 and September 5, 2022, were retrieved from databases, including EMBASE, PubMed, Cochrane Library, the China Biology Medicine disk, China National Knowledge Infrastructure, and Wanfang databases. We included clinical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Similarly, in Europe, the annual incidence of OHCA among adults ranges from 67 to 170 per 100,000, with discharge survival rates varying from 0% to 18% [ 5 ]. In China, more than 540,000 individuals experience OHCA each year, but the survival rate remains at approximately 2% [ 6 ]. These statistics underscore that OHCA, despite regional disparities, has emerged as a substantial public health challenge, imperiling the well-being of citizens [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in Europe, the annual incidence of OHCA among adults ranges from 67 to 170 per 100,000, with discharge survival rates varying from 0% to 18% [ 5 ]. In China, more than 540,000 individuals experience OHCA each year, but the survival rate remains at approximately 2% [ 6 ]. These statistics underscore that OHCA, despite regional disparities, has emerged as a substantial public health challenge, imperiling the well-being of citizens [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, many studies have shown that the reasons behind bystanders' inconsistent rst aid attitudes and behaviors are related to the level of rst aid knowledge and willingness [20][21][22] . Up to 93.2% of people express willingness to learn rst aid knowledge and skills [23] , but the rst-witness rescue rate is only 18.0% [24] , lower than the world average (20%~70%) [25] . It is precisely because of the "gap" in cognition and behavior that hinders the public's implementation of on-site rst aid.…”
mentioning
confidence: 99%